Analisis Fatwa Dr. Syauqi Ibrahim ‘Allam Tentang Peribadatan Non Muslim Prespektif Hukum Islam - Maftuha, Abda' Balya; Fuad, A. Jauhar; Anwar, Saiful (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2024)
Islam is a universal religion that explains various rules related to procedures for worship and interaction between humans. However, the number of cases of religious intolerance remains high. In Indonesia, as a Muslim-majority country alone, between 2019-2023 there were 65 cases of religious intolerance. Based on this reality, the author tries to analyze the fatwa of the Grand Mufti of Egypt, Dr. Syauqi Ibrahim 'Allam who discussed the status of non-Muslim worship. These fatwas were collected in one of his works, Fiqhu al-Wathon wa al-Muwathonah. Thus, this research seeks to analyze the methods and results of istinbath carried out by Dr. Syauqi Ibrahim 'Allam in answering this problem. To achieve this goal, the method used in this research is a qualitative research method that has a content analysis style by taking sources from various studies. The results of this research explain that non-Muslim worship is a place in which security must be guaranteed. This is a form of tolerance and fulfillment of the rights of fellow citizens. In his fatwa, he took sources from various literature of fiqh scholars, so that in each fatwa he was considered in accordance with the concept of thought of one of the four imams of the school of thought. However, he also does not mind when there are differences in fatwas, because differences in social conditions also make it possible for differences in fatwas to emerge.